KEABSAHAN PRODUK REDISTRIBUSI TANAH YANG DITERBITKAN DIATAS TANAH ASET NEGARA (EX-BLBI): STUDI KASUS PUTUSAN PN CIBINONG NO. 182/PDT.G/2021/PN CBI): Studi Kasus Putusan Pn Cibinong No. 182/Pdt.G/2021/Pn Cbi - Siti Aisyah; Rika Amelia; Jathu Puspitosari (Legal Standing : Jurnal Ilmu Hukum, 2026)
The land case in Cikopomayak and Neglasari Villages, Bogor Regency, presents unique legal complexities. This study analyzes the legal conflict that arose between the settlement process for Bank Indonesia Liquidity Assistance (BLBI) assets and the implementation of the land redistribution program, focusing on the cancellation of 300 certificates in Cikopo Mayak, Jasinga, Bogor. The case stemmed from the confiscation of land by the Indonesian Bank Restructuring Agency (IBRA) in 1999 as part of BLBI debt collection. The land was then allocated for the land redistribution program by the ATR/BPN, with certificates issued to the community from 2015–2020. However, Cibinong District Court Decision No. 182/Pdt.G/2021/PN.Cbi determined that the land was still under state confiscation status for the settlement of BLBI obligor obligations, resulting in the cancellation of the issued certificates. The findings indicate that the lack of synchronized coordination between institutions and the unclear status of the assets were the main factors in the dispute. This case highlights the need for policy reform and procedural certainty to ensure that the settlement of BLBI assets does not compromise the rights of recipients of the redistribution funds and to prevent similar conflicts in the future.